2018
DOI: 10.1101/gad.314856.118
|View full text |Cite
|
Sign up to set email alerts
|

A length-dependent evolutionarily conserved pathway controls nuclear export of circular RNAs

Abstract: Circular RNAs (circRNAs) are generated from many protein-coding genes. Most accumulate in the cytoplasm, but how circRNA localization or nuclear export is controlled remains unclear. Using RNAi screening, we found that depletion of the DExH/D-box helicase Hel25E results in nuclear accumulation of long (>800-nucleotide), but not short, circRNAs. The human homologs of Hel25E similarly regulate circRNA localization, as depletion of UAP56 (DDX39B) or URH49 (DDX39A) causes long and short circRNAs, respectively, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
211
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(215 citation statements)
references
References 38 publications
2
211
0
2
Order By: Relevance
“…To determine the subcellular localization of circE7, cells were fractionated and nuclear and cytoplasmic fractions confirmed with MALAT1 and 18S or β-actin, respectively. Consistent with the behavior of other translated circRNAs 20,22,23,24 , RT-PCR confirmed that the majority of circE7 (~60%) localized to the cytoplasm ( Fig. 2e).…”
Section: Resultssupporting
confidence: 80%
“…To determine the subcellular localization of circE7, cells were fractionated and nuclear and cytoplasmic fractions confirmed with MALAT1 and 18S or β-actin, respectively. Consistent with the behavior of other translated circRNAs 20,22,23,24 , RT-PCR confirmed that the majority of circE7 (~60%) localized to the cytoplasm ( Fig. 2e).…”
Section: Resultssupporting
confidence: 80%
“…Alurepeats in primates) or facilitated by interactions between flanking intronbound RNA-binding proteins (RBPs) 13,15,19 . circRNAs are largely localized to the cell cytoplasm [9][10][11][12][13][14] , and recent evidence suggests that nuclear export of circRNAs in human cells is influenced by the size of the given molecules 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, knockdown experiments have shown that nuclear export of larger circRNAs (>800 nucleotides) are dependent on DExH/D-box helicase UAP56 (DDX39B), whereas smaller species are dependent on URH49 (DDX39A) 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of circRNAs originate from exons, although there have been studies showing that they are produced from a variety of regions in the genome, including introns, exons, and UTR regions. The cytoplasm is host to the majority of circRNAs (Kristensen et al, 2018), but there is recent evidence of certain circRNAs enriched in the nucleus and controlled or modulated by sequence length (Huang et al, 2018). Interestingly, most circRNAs are not more abundant when compared to corresponding mRNA transcripts, but circRNAs exhibit greater half-lives demonstrating their increased stability (Kristensen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%